Degradation of 1,2,3,4-Tetrachlorobenzene by Pseudomonas chlororaphis RW71 - Potrawfke, Thomas (American Society for Microbiology, 1998)
Pseudomonas chlororaphis RW71 mineralized 1,2,3,4-tetrachlorobenzene, a highly recalcitrant pollutant hitherto not known to be degraded by pure cultures, as a sole source of carbon and energy, thereby releasing stoichiometric amounts of chloride. The transient excretion of tetrachlorocatechol in the early growth phase suggests an initial attack by a dioxygenase to form the corresponding dihydrodiol which rearomatizes to the catechol. The activity of chlorocatechol 1,2-dioxygenase in crude cell extracts was found to be extraordinarily high towards 3-chlorocatechol (ratio of 2.6 compared to catechol) and other chlorocatechols, including tetrachlorocatechol, which was transformed at a low but significant rate. Further identification of tetrachloromuconic acid, 2,3,5-trichlorodienelactone, 2,3,5-trichloromaleyl acetic acid, and 2,4-dichloro-3-oxoadipic acid as their methyl esters, together with high specific enzyme activities for chlorinated substrates, implicated a functioning chlorocatechol pathway to be induced during growth.